PENGARUH KUALITAS PRODUK, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI KATERING YVONNE’S - Dilan Hatma; Bonifasius Nainggolan (LPPM Universitas Asa Indonesia, 2021)
The purpose of this research is to determine the effect of product quality, promotion, and quality service on purchase decision at the Catering Yvonnes. The population in this study are the customers of 100 people by accidental sampling method. The data collection by accidental technique using the designed questionnaire. The questionnaire has been tested of its validity dan reliability prior to distribution. Data were analyzed by descriptive and quantitative. The regression analysis started with the classical assumption test (normality, multicolinierity, heteroscedasticity and linierity test) afterward by multiple linier regression analysis. The model determined by the hypotheses testing applied F, T test and correlation test and the coefficient of determination (R2). The results showed that product quality has a significant influence on purchase decision, promotion has a significant effect on purchase decision, quality service has a significant effect on purchase decision, where all varables have a positive effect on purchase decision simultaneously at the Catering Yvonne’s.